PRIMARY PREVENTION OF POSTOPERATIVE REFLUX DISEASE - V. L. Martynov; N. Yu. Orlinskaya; D. G. Kolchin; V. A. Kurilov; I. B. Kazantsev (Бюллетень сибирской медицины)
Creation of anastomoses between hollow organs of the abdominal cavity, retroperitoneal space and the small intestine always raises the question of the prevention of reflux from the small intestine into the cavity drained the esophagus, stomach, gallbladder, liver outer duct cysts of the liver and pancreas. After surgery, any reflux becomes pathological. Reflux – is an obligate precancer. So, throw the bile and pancreatic juices in the stomach, the stump of the stomach, esophagus contributes to reflux esophagitis, reflux gastritis, ulcers and gastric cancer, or a stump. After an internal drainage of cavity formation in the small intestine develops postoperative reflux disease, which is caused by the actions of the surgeon who tried sincerely to help the patient. It is possible to give the definition of such states “Iatrogenic Postoperative Reflux Disease”.The aim of this work was to develop and put into practice a “cap” on the afferent loop of the small intestine, do not migrate into the gut lumen, with an internal cavity drainage structures of the abdominal cavity and retroperitoneal space and to evaluate clinical outcomes. As a result, the authors have developed a way to create a “cap” on a loop of the small intestine, which is used for the drainage of cavity formation, conducted research on its safety, proper functioning, accessibility, analyzed the clinical situation offers. For drainage of cavernous fistula formation impose between him and a loop of small intestine 40–50 cm from the Treitz ligament. Form a intestine anastomosis by Brown.Above this junction length leads to the formation of the drained portion of the small intestine is about 10 cm, in the middle of which impose a “stub”. Length of discharge from the drainage area of education of the small intestine to interintestinal Brownian anastomosis is about 30 cm. To form a “plug” free land use of the greater omentum, through which by puncture-poke perform ligature of non-absorbable polypropylene material. The developed method for forming a “plug” does not cause drastic changes in the ischemic zone of operation, followed by necrosis of the bowel wall and migration "stub" into the lumen, and its efficiency is demonstrated by clinical observation of microcirculation studies, the results of the water sample, and radiological studies. Way to create a “stub” is promising for internal drainage of abdominal structures of the abdominal cavity and retroperitoneal space, to form a nutrient anti reflux eyunostomy.